Serological survey of paratuberculosis in dairy cattle in Garfagnana district (Tuscany) - GALIERO, A.; FRATINI, F.; BRAVI, P.; TURCHI, B.; CASANOVI, E.; CERRI, D. (Journal of the Hellenic Veterinary Medical Society, 2018)
Mycobacterium avium subsp. paratuberculosis (Map) is the agent of a chronic, progressive granulomatous enteritis in ruminants known as Johne’s disease or paratuberculosis. Nowadays, the interest regarding this pathogen is increasing not only because Map causes economic losses, but it has also been suggested as a potential risk factor for the development of human diseases such as Crohn disease, autoimmune diseases like type-1 diabetes, sarcoidosis, multiple sclerosis and Hashimoto’s thyroiditis. The aim of our study was to determine the presence of paratuberculosis in Garfagnana (Tuscany, Italy) where raw milk is not submitted to pasteurization, but it is directly sold to consumers or it is destined for cheese making without the employment of heat treatment. The survey was conducted in Garfagnana district where there are 17 herds which produce and market bovine milk for direct human consumption. Serum samples (n=162) were obtained form 16 herds and were analyzed performing ELISA ID screen® Paratuberculosis Indirect screening test (ID.VET, Montpellier, France) and positive samples were tested with ELISA ID screen® Paratuberculosis Indirect confirmation test (ID.VET, Montpellier, France), according to the instructions provided by the manufacturer. The analysis performed by ELISA revealed that the true seroprevalence was 29.1% at the herd level and 4.6% at the animal level. In our opinion, although ELISA is a very useful tool to screen herds for paratuberculosis, more studies should be carried out in our territory combining serological data with cultural and PCR analysis.